Information assets in leisure historic motor sport: a case study in Australia - Joseph, Pauline (Routledge, 2017)
© 2017 Canadian Association for Leisure Studies / Association canadienne d’études en loisir This paper investigates the information assets of historic motor sport community-based organisations in Australia and considers their significance. The study covers the regulator of motor sport, the Confederation of Australian Motor Sport Ltd. (CAMS) and its offices in Australia, and an affiliated club, the Vintage Sports Car Club in Western Australia (WA). It determines what information enthusiasts need from CAMS and how they evaluate their information-seeking experiences. It then focuses on responses to the proposal for a common system that will sustainably manage community-based information assets. It identifies motor sport’s significant information assets and the risks associated with their current information management practices and highlights the role of the sport’s governing body in ensuring that individual clubs’ records and community archives are managed and preserved. It signals the value of a custodian to sustainably manage the information assets of these organisations and preserve their sporting identity, culture and community history. Motor sport enthusiasts support their governing body providing such services.